The effect of abusive supervision variability on work–family conflict: The role of psychological detachment and optimism - Wang, Shuwei; Lin, Xiaoxin; Wu, Jun (Frontiers in Psychology, 2023)
Although a number of studies have examined the effects of abusive supervision variability, which refers to leaders engaging in differential abuse towards different subordinates within the team on work-related outcomes, scant research has investigated whether and how abusive supervision variability affect non-work outcomes. Drawing on the conservation of resource theory, the current study explores how abusive supervision variability affects work-family conflict through psychological detachment, as well as the moderating role of optimism. Results based on a survey of 260 employees from 9 companies show that abusive supervision variability is significantly and positively related to work-family conflict. Psychological detachment mediates the effect of abusive supervision variability on work-family conflict. Optimism moderates the relationship between abusive supervision variability and psychological detachment and the indirect effects of abusive supervision variability on work-family conflict through psychological detachment. This study extends the literature on the effects of abusive supervision variability and provides several important practical implications.